Engaging tuberculosis-affected people in investment decisions: applying a people-centered design approach in Viet Nam - Rachel Forse; Phuong-Tra Vu; Trang Nghiem; Luan Nguyen Quang Vo; Andrew James Codlin; Ngoc B. Pham; Ngan Huynh; Thanh Thi Nguyen; Luu Quang Vinh; Nguyen Thi Kim Ngan; Nguyen Thi Thuy; Pham Viet Phuong Khanh; et al. (BMC Public Health, 2026)
Abstract Background Tuberculosis (TB) remains the leading cause of death from an infectious disease globally, yet financing for the TB response continues to fall far short of identified needs. Decisions about how resources are allocated are often made with limited engagement of people directly affected by TB, potentially overlooking lived experiences and community-defined priorities. This study was implemented in Viet Nam to align future TB investments with community-defined priorities and programmatic feasibility. This paper describes the process and its application to priority setting and intervention selection alongside national planning processes. Methods This was a participatory co-design study guided by a people-centered design framework. The process integrated qualitative data collection and deliberative stakeholder engagement across three phases: Discover (qualitative interviews and focus groups to identify challenges), Define (stakeholder workshops to prioritize challenges and co-develop an evaluation framework), and Develop (structured prioritization assessment and selection of an intervention). In the Discover phase, 88 participants identified challenges across the TB care cascade. In the Define and Develop phases, decision-making was overseen by a diverse 21-member Leadership Group. Participants co-developed an evaluation framework across three domains (fit and desirability, potential impact, and feasibility), which was used to assess and rank potential investment opportunities. Facilitation strategies, including equal voting rights and anonymous ranking, were applied to promote equitable participation. Results In the Discover phase, 15 key challenges across the TB care cascade were identified and reframed as opportunities for improvement. In the Define phase, stakeholders applied the evaluation framework to assess 19 innovation categories. Three intervention areas were shortlisted for detailed consideration: computer-aided detection software for chest X-ray interpretation, paper-free data systems, and social and financial protection. In the Develop phase, structured scoring and deliberation, including consideration of feasibility and the existing funding landscape, led to the selection of social and financial protection as the intervention for near-term investment and implementation. Conclusions Participatory co-design enabled TB-affected people and health system stakeholders to directly contribute to early-stage investment prioritization within Viet Nam’s TB response. The selection of social and financial protection reflects both lived economic challenges and system-level considerations, highlighting the value of participatory approaches in identifying locally relevant priorities that may be underemphasized in conventional funding processes.